A GIS-Based Framework for Assessing Urban Heat Island Phenomena - Desai, Gautam (Journal of Progress in Civil Engineering, 2025)
This research presents a detailed urban planning framework that utilizes sophisticated GIS tools to drive significant climate action in urban areas. By combining high-resolution maps of land surface temperature with climate forecast data, the methodology effectively pinpoints critical “hot spots” where the urban heat island effect is most severe. Using surface radiation data as an indicator for analyzing urban microclimates, the study prioritizes specific sub-areas for intervention based on both the intensity of heat and anticipated population growth. The approach incorporates evaluations of public spaces at the city block level, achieved through thorough on-site surveys and demographic analysis. This evaluation employs the Universal Thermal Climate Index (UTCI) alongside digital parametric 3-D modeling tools. This integrated process generates assessments of current conditions as well as future projections-both in typical scenarios and under best-practice implementation-by taking into account increases in population density and planned infrastructure developments. The resulting design recommendations are rooted in evidence based urban climate factor diagrams and are informed by comparing models of districts experiencing varying degrees of heat stress. Ultimately, this framework offers urban planners a data-driven and practical guide for reducing urban heat, lowering energy demands, and improving the overall quality of civic life.